Farmer's organizations are capable of managing their affairs - Belloncle, Guy (Technical Centre for Agricultural and Rural Cooperation, 1992)
Guy Belloncle is Professor of Sociology at the University of Tours in France. He is consultant sociologist to many development projects, both governmental and non-governmental, which promote farmers organizations. After the failure of many...